Adaptation and validation of the instrument "Children Care Quality at Hospital" for portuguese - Loureiro, Fernanda Manuela (2019)
Objective: adapt and validate the instrument Children Care Quality at Hospital (CCQH) to assess the quality of nursing care of hospitalized children for the Portuguese language of Portugal. Materials and Methods: content, language, and conceptual validity methodological study, with translation, feedback, and reflection. A non-probabilistic simple was used of 252 children between 7 and 11 years of age, hospitalized due to acute disease in nine services of six Portuguese hospitals. The reliability and validity of the results were determinedm to measure the psychometric properties of the instrument. Construct validity was calculated through exploratory factor analysis of main components with Varimax rotation and the internal consistency by determining the Cronbach’s alpha coefficient. Results: the internal consistency has adequate psychometric characteristics suitable for the Portuguese population (Cronbach’s alpha values between 0.66 and 0.82). The instrument maintained 49 items grouped into three categories: characteristics, activities, and environment. The psychometric characteristics of the CCQH, adapted and validated for Portuguese, guarantees its reliability and validity to measure satisfaction with the quality of nursing care from the perspective of school-aged children. Conclusions: the instrument could be used to assess children’s satisfaction with the quality of nursing care during their hospitalization